2009
DOI: 10.3945/ajcn.2009.28216
|View full text |Cite
|
Sign up to set email alerts
|

Green tea consumption is associated with depressive symptoms in the elderly

Abstract: A more frequent consumption of green tea was associated with a lower prevalence of depressive symptoms in the community-dwelling older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 29 publications
7
94
2
1
Order By: Relevance
“…Results from these studies suggest that green tea can be useful for the several health conditions. It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37].…”
Section: The Health Effects Of Green Teasupporting
confidence: 78%
“…Results from these studies suggest that green tea can be useful for the several health conditions. It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37].…”
Section: The Health Effects Of Green Teasupporting
confidence: 78%
“…In one article conducted in South Korea, it has been indicated that prevalence of sugar-sweetened beverages like sports/energy drinks, coffee/tea products, and flavored milk are increasing among adults from 62% to 69% and by the elderly from 30% to 47% between 2001 and 2009. It was higher among high socio-economic status stated by Niu et al [27]. In other study, their results showed that 30% of athletes drank more than 1 mg/kg/day caffeine and the majority of high-level Canadian athletes consume dietary caffeine primarily in the form of coffee [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hintikka et al (2005) observed an inverse relationship between daily tea drinking and the risk of depression in a relatively large Finnish general population sample. Niu et al (2009) observed that more frequent consumption of green tea was associated with a lower prevalence of depressive symptoms in community-dwelling elderly. Zhu et al (2012) observed that green tea polyphenol extract exerted antidepressant-like effects in a mouse model, and the mechanism might involve inhibition of the hypothalamic-pituitaryadrenal axis.…”
Section: Tea Consumptionmentioning
confidence: 94%